2017
DOI: 10.5194/tc-11-2247-2017
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of the drainage system of a Himalayan debris-covered glacier, and its relationship with patterns of mass loss

Abstract: Abstract. We provide the first synoptic view of the drainage system of a Himalayan debris-covered glacier and its evolution through time, based on speleological exploration and satellite image analysis of Ngozumpa Glacier, Nepal. The drainage system has several linked components: (1) a seasonal subglacial drainage system below the upper ablation zone; (2) supraglacial channels, allowing efficient meltwater transport across parts of the upper ablation zone; (3) submarginal channels, allowing long-distance trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
122
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(128 citation statements)
references
References 28 publications
6
122
0
Order By: Relevance
“…In the upper ablation zone of debris‐covered glaciers, observations of increased summer velocities on Lirung and Ngozumpa Glaciers, suggest that basal‐sliding is promoted where surface meltwater is routed the glacier bed (e.g. via crevasses) (Kraaijenbrink et al ., ; Benn et al ., ). Seasonal velocity observations are lacking for Khumbu Glacier; however, it is likely that surface‐bed hydrological connections play a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…In the upper ablation zone of debris‐covered glaciers, observations of increased summer velocities on Lirung and Ngozumpa Glaciers, suggest that basal‐sliding is promoted where surface meltwater is routed the glacier bed (e.g. via crevasses) (Kraaijenbrink et al ., ; Benn et al ., ). Seasonal velocity observations are lacking for Khumbu Glacier; however, it is likely that surface‐bed hydrological connections play a similar role.…”
Section: Discussionmentioning
confidence: 99%
“…This drainage process seems similar to the closure and opening (connection) of an englacial conduit for a supraglacial lake on a debris-covered glacier (Benn et al, 2001;Gulley and Benn, 2007;Gulley et al, 2009). Supraglacial lakes have a seasonal variability and can be transient or recurring, depending on the connectivity to englacial network (Miles et al, 2017a, b;Benn et al, 2017;Narama et al, 2017). The formation and sudden drainage of supraglacial ponds have also occurred in the Cordillera Blanca, Peru (Emmer et al 2015).…”
Section: Geomorphological Characteristics Of Tunnel-type Short-livedmentioning
confidence: 88%
“…After drainage, vertical subsidence occurs along the subsurface channel in the debris landform. Such short-lived glacial lake types recur when their ice tunnel closes, similar to that on a supraglacial lake on a glacier or on a debris-covered glacier (Kropáček, et al, 2015;Benn et al, 2017;Narama et al, 2017). For example, at Angisay Glacier in the Teskey Range (Fig.…”
Section: Geomorphological Characteristics Of Tunnel-type Short-livedmentioning
confidence: 98%
See 1 more Smart Citation
“…However, an analysis of the diurnal 5 cycle (Figure 14) showed that DHSVM-GDM responds too rapidly to the ice melt production and that the representation of the water storage within the glaciers needs to be improved. Further improvements should be based on studies that analyze the mechanisms of glaciers drainage systems in the Khumbu region and their influence on glaciers outflow (e.g., Gulley et al, 2009;Benn et al, 2017). These studies show that englacial conduits and supraglacial channels, ponds and lakes play a key role in the response of glaciers: DHSVM-GDM could thus be upgraded by implementing a parameterization of such systems and 10 delay the response of glacierized areas, as successfully proposed, for instance, in the model developed by Flowers and Clarke (2002).…”
mentioning
confidence: 99%